2017
DOI: 10.1002/cpim.18
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Immunodiffusion Assay for Detecting Specific Antibodies (Ouchterlony)

Abstract: The method first described by Ouchterlony in 1948 is a classic and simple technique that permits evaluation and comparison of antibodies in animal or human sera directed against protein or complex carbohydrate antigens. It is a low-tech procedure that may provide information on the relative quantity of antibody activity and the nature of the antigenic epitopes in different preparations. © 2017 by John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 3 publications
0
13
0
3
Order By: Relevance
“…The ODIT is the most useful serological technique for the detection of specific antibodies in sera, or for identifying viral antigen or antibodies in bursa. The ODIT is used to detect prominent white line of precipitation between bursal homogenates of the peripheral wells and known positive anti-IBDV hyper-immune serum of the central well due to antigen and antibody reaction (Hornbeck, 2017). Our data demonstrated that, in case of ODIT, hemorrhagic and edematous bursal homogenates were found positive for IBDV.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The ODIT is the most useful serological technique for the detection of specific antibodies in sera, or for identifying viral antigen or antibodies in bursa. The ODIT is used to detect prominent white line of precipitation between bursal homogenates of the peripheral wells and known positive anti-IBDV hyper-immune serum of the central well due to antigen and antibody reaction (Hornbeck, 2017). Our data demonstrated that, in case of ODIT, hemorrhagic and edematous bursal homogenates were found positive for IBDV.…”
Section: Resultsmentioning
confidence: 67%
“…ODIT is also familiar as passive double immunodiffusion or AGID test. ODIT is a simple method to detect specific antibody and measure antigenicity (Hornbeck, 2017). It is simplest but least sensitive serological method (Sali, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent performance in double immunodiffusion (DID) assay by using mini gel cassette DID was commonly used as a screening test for the monitoring of binding of antibody and antigen [53]. For conventional DID assay, the sample wells in gel are typically prepared by punching such as multiple-well patterns after the gel is solidified.…”
Section: Resultsmentioning
confidence: 99%
“…The method used here was first described by Ouchterlony in 1948 42 . It is a classic and simple technique that evaluates antibodies in animal or human sera 43,44 .…”
Section: Methodsmentioning
confidence: 99%